Future scenarios and forecasts for the evolution of accounting and auditing in Ukraine post-war. - Mykhalkiv, A; Kostash, T; Andrusiak, V; Dovzhyk, O; Ponomarova, N (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Scenario analysis is widely applied in strategic economic planning to explore alternative futures under varying assumptions and uncertainties. Originating from decision theory, systems thinking, and complexity science, it supports informed judgment in uncertain environments. Despite its broad application, previous research on accounting and auditing reforms has predominantly concentrated on stable economies, with minimal emphasis on countries recovering from conflict. This study examines the future trajectories of accounting and auditing practices in post-war Ukraine using a scenario analysis framework. Data were collected through the Delphi method, incorporating expert interviews and survey questionnaires. Analytical techniques included the Statistical Package for the Social Sciences (SPSS) and Partial Least Squares Structural Equation Modelling (PLS-SEM), supplemented by bootstrapping for result validation. The analysis reveals that Scenario 1, referred to as "Digital Reinvention," has a statistically significant impact on the projected development of accounting and auditing in Ukraine's post-war context. In contrast, Scenarios 2 and 3, labeled "Gradual Compliance" and "Regulatory Stagnation," do not exhibit significant associations with the evolution of thefield. The findings indicate that the three exogenous variables together explain approximately 41.2% of the total variance in the endogenous variable, demonstrating a moderate predictive capacity of the model. This suggests that Ukraine’s post-conflict financial landscape is likely to be influenced predominantly by digital transformation, institutional modernization, full adoption of International Financial Reporting Standards (IFRS), and the implementation of artificial intelligence and blockchain technologies to enhance financial transparency and audit reliability in the emerging economic environment.